Unsaturated Mo in Mo4O4N3 for efficient catalytic transfer hydrogenation of nitrobenzene using stoichiometric hydrazine hydrate. Issue 21 (7th October 2021) - Luo, Shicheng; Long, Yu; Liang, Kun; Qin, Jiaheng; Qiao, Yi; Li, Jing; Yang, Guangxue; Ma, Jiantai
Abstract : Unsaturated Mo in Mo4 O4 N3 exhibited efficient catalytic activity for transfer hydrogenation of nitrobenzene using stoichiometric N2 H4 ·H2 O. Abstract : Transfer hydrogenation of nitroarenes to the corresponding anilines using hydrazine hydrate and non-noble metal catalysts has already been widely studied. However, the toxicity resulting from excess hydrazine hydrate and the high reaction temperature limit its industrial application. Herein, a novel N-doped molybdenum oxide compound (Mo4 O4 N3 ) was in situ prepared from g-C3 N4 and (NH4 )6 Mo7 O24 ·4H2 O (AHM). The as-prepared Mo4 O4 N3 can achieve a 99% yield of aniline using a stoichiometric molar ratio of hydrazine hydrate (–NO2 : N2 H4 ·H2 O = 1 : 1.5) at room temperature for 50 minutes. Mechanistic experiments and characterization techniques indicate that the acidic sites of unsaturated Mo in Mo4 O4 N3 can efficiently activate N2 H4 molecules to form active hydrogen species for catalytic transfer hydrogenation of nitroarenes without the generation of hazardous NH3 . Besides, Mo4 O4 N3 still exhibited excellent catalytic performance for the large-scale reaction without solvent. This work may offer a feasible and efficient strategy for arylamine production.